Lo que el voto se llevó. La des-composición del pacto posrevolucionario en México. De Willibald Sonnleitner - Marván Laborde, María (El Colegio de México, 2021)
This is a book about the sociology of the Mexican vote. With an original methodology and a multidisciplinary approach, the author is able to do different kind of radiologies in different geographical scales.  It is possible to observe macro tendencies as well as micro behavior of the voters. The analysis macro goes from 1961 to 2015; the analysis micro (by electoral sections) starts from 1991 on. The author proves that the decomposition of the post-revolutionary pact was uneven, at different rhythms changing from one geographical zone to another. Mexico stops having a hegemonic party´s system to have a multiparty system competitive and unstable. Throughout the book the theory of modernization is challenged with empirical evidence. The author proofs that despite of the multifactorial causes to different kinds of votes it is possible to study how the Mexicans vote.